2015
DOI: 10.17577/ijertv4is050635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forging Condition on Mechanical Properties of Al/SiC Metal Matrix Composites

Abstract: The objective of the research work to investigate effect of forging condition on mechanical properties of Al/SiC composites prepared in open die at the temperature of 450 °C with three different stages then specimens are aged at T6 conditions. Forged specimens subjected tensile, compression and hardness tests to evaluate effect of forging levels on Al/SiC composites. The effect of plastic deformation and high temperature during forging led to a recrystallization of the Al/SiC matrix with a grain refinement. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The aforementioned improvement properties were adduced to even dispersion of fly ash particles and grain structure refinement as percentage rolling reduction increases. In Hanamantraygouda and Shivakumar (2015), Al-SiC based composites subjected to hot forging at a temperature of 450 C and aged at T6 conditions were examined. It was shown that the treated Al-SiC based composites exhibited improved tensile strength, compressive strength and hardness properties although with insignificant detrimental effect on ductility.…”
Section: Other Thermomechanical Treatmentsmentioning
confidence: 99%
“…The aforementioned improvement properties were adduced to even dispersion of fly ash particles and grain structure refinement as percentage rolling reduction increases. In Hanamantraygouda and Shivakumar (2015), Al-SiC based composites subjected to hot forging at a temperature of 450 C and aged at T6 conditions were examined. It was shown that the treated Al-SiC based composites exhibited improved tensile strength, compressive strength and hardness properties although with insignificant detrimental effect on ductility.…”
Section: Other Thermomechanical Treatmentsmentioning
confidence: 99%
“…In addition, there is only a small fraction of fracture surface that is dominated by small dimples. These small dimples are generally distributed at the boundaries between the fits, probably due to the ductile rupture of the magnesium matrix This has large number of dimple shaped structures no crack found (20). The presence of dimples displays the typical ductile fracture of the matrix alloy.…”
Section: 3fractographymentioning
confidence: 99%
“…MMNCs can be formed by conventional deformation processes such as rolling, extrusion or forging, among which forging has been used as the secondary processing for its excellent preferential axial alignment of discontinuous fibers as well as compressive hydrostatic state of stress [7][8]. The forged nanocomposites exhibit reduced porosity, a more uniform particle distribution and improved ductility [9][10].…”
Section: Introductionmentioning
confidence: 99%